Effects of Eurotium Cristatum on soybean (Glycine max L.) polyphenols and the inhibitory ability of soybean polyphenols on acetylcholinesterase under different conditions - Shuo-shuo Shi; Ting Hu (Food Chemistry: X, 2024)
Most phenolic compounds in beans exist in complex, insoluble binding forms that bind to cell wall components via ether, ester, or glucoside bonds. In the process of solid-state fermentation, Eurotium Cristatum can produce many hydrolase enzymes, such as α-amylase, pectinase, cellulase and β-glucosidase, which can effectively hydrolyze ether, ester or glucoside bond, release bound polyphenols, and increase polyphenol content in soybeans. When the fermentation conditions of soybean were fermentation time 12 days, inoculation amount 15% and initial pH 2, the content of free polyphenols in fermented soybean was 2.79 mg GAE/g d.w, which was 4.98 times that of unfermented soybean. The contents of bound polyphenols and total phenols in fermented soybean were 0.62 mg GAE/g d.w and 3.41 mg GAE/g d.w, respectively, which were 2.38 times and 4.16 times of those in unfermented soybean. At the same time, the inhibitory effect of free polyphenols in fermented soybean on acetylcholinesterase reached 91.51%. Thus, our results demonstrated that solid state fermentation and Eurotium Cristatum can be used as an effective way to increase soybean polyphenol content and combat Alzheimer's disease.